USER EXPERIENCE JOURNEY WITH MULTIPLE DEVICES AND TELEPRESENCE DURING QUARANTINE - Renzi, Adriano Bernardo; Meira, Camila; Ribeiro, Ana Clara; Correa, Matheus; Bittencourt, Mariana; Souza, Julia; Lana, Kathryn (Ergodesign & HCI; v. 8 n. 1 (2020): Ergodesign & HCI, n.1, v.8, jan-jun (2020), 2020)
Many cities and countries around the world started quarantine and city lockdowns to diminish the spread of Covid-19, configuring the end of the 20th century: the century of technology. The fast growing technology and communication possibilities upgrades human-computer interactions from industrial development before computing to connecting users to many computers in a dynamic ecosystem in pervasive experiences. The new social challenges from quarantine and self-preservation takes home isolation, technology, Internet, family, education, work and communication to surface new sense of things and interactions. Each generation has their own perspectives and mental models about the pandemic times and the use of technology, creating themselves the necessary bridges between channels to make their experience journeys easier and to reach objectives. This research focus on understanding how quarantine and social isolation in Rio de Janeiro affected the 4 generations’ interaction with digital devices and he diversity of channels, how it affected their own sense of space and isolation, influencing communication, entertainment, work and learning. The research was conducted during the quarantine official decree in the city – from March 16th to June 1st.